Improving reading comprehension using metacognitive strategies - Bustami Usman; Zulfadli A. Aziz; Nova Riska Absida (English Education Journal, 2017)
This research discusses the use of metacognitive strategies to improve students’ reading comprehension. The data was obtained from 50 students from two classes, one an Experimental Group (EG) and the other a Control Group (CG). The instruments used for collecting the data were tests (a pre-test and a post-test) and a questionnaire. The data collection was divided into four different phases of the research; the pre-test, the treatment, the post-test and the questionnaire. The results of the test were analyzed quantitatively to find any significant differences between the two groups. The results showed that there was a statistically significant difference after using metacognitive strategies in the reading comprehension of the EG students compared to those in the CG, who did not use metacognitive strategies for reading comprehension. The t-value (6.03) t-table (2.01) meant that the alternative hypothesis was accepted. Further, the results from the questionnaires also showed the positive impact, viz: the positive classroom atmosphere, the improved motivation to learn, the improvements in students’ knowledge and so on.